Optimizing Soil Health and Maize Yield Under Salinity Stress with Compost and Sulfur Nanoparticles - Mahmoud M. A. Shabana; Nevien Elhawat; Mohamed A. Abd El-Aziz; S. H. Abd Elghany; Asmaa F. M. Badawy; Tarek Alshaal (Plants)
Soil salinity poses a significant challenge to agricultural productivity, particularly in arid and semi-arid regions. This study explores the effect of compost, elemental sulfur (ES), sulfur nanoparticles (SNPs), and their combinations, i.e., compost + ES and compost + SNPs, to improve soil properties and maize productivity across a range of salinity levels (EC1 = 3.68, EC2 = 6.15, EC3 = 8.34, and EC4 = 12.18 dS/m). We hypothesized that integrating compost with ES or SNPs would enhance soil quality and maize performance more effectively than individual treatments. Results validated this hypothesis, showing that compost increased soil organic matter (SOM) by 1.33 times, reduced sodium adsorption ratio (SAR) by 33%, and boosted maize grain yield by 40% in moderately saline soils (6.15 dS/m). ES and SNPs lowered soil pH by 0.8–1.2 units and improved phosphorus availability by 25–30%. The compost–SNP combination delivered the most significant improvements, enhancing infiltration rate by 60%, total porosity by 15%, and straw yield by 50% in highly saline soils (12.18 dS/m). Additionally, plant height, cob length, and chlorophyll content increased by 20%, 22%, and 40%, respectively, with combined treatments. These findings highlight the efficacy of integrated amendments in alleviating salinity stress, offering a promising strategy for sustainable agriculture in saline environments.